Authentication Technologies for Cloud Computing, IoT and Big Data - Alginahi, Yasser M.; Kabir, Muhammad Nomani (Security., 2019)
The fundamentals of authentication technologies, i.e., information security, cryptographic algorithms, data authentication algorithms, watermarking, and biometric authentication are presented with comprehensive examples and algorithmic details. The book includes some attractive topics in the era of big data, IoT, cloud computing, i.e., lightweight security algorithms for IoT applications, identification schemes for post-quantum era, authentication for cloud application, cryptographic algorithms on FPGA for cloud application and data protection laws. In addition, the book provides future research directions and open problems related to the evolution of technologies.